2002
DOI: 10.1038/sj.bjc.6600414
|View full text |Cite
|
Sign up to set email alerts
|

Oxaliplatin plus raltitrexed and leucovorin-modulated 5-fluorouracil i.v. bolus: a salvage regimen for colorectal cancer patients

Abstract: The aim of the present study was to define the activity and tolerability of a triplet regimen including oxaliplatin 130 mg m 72 (2 h i.v. infusion) and raltitrexed 3.0 mg m 72 (15 min i.v. infusion) given on day 1, followed by levo-folinic acid 250 mg m 72 (2 h i.v. infusion) and 5-fluorouracil 1050 mg m 72 i.v. bolus on day 2, every 2 weeks, in pretreated colorectal cancer patients. From April 1999 to December 2000, 50 patients were enrolled: 26 were males and 24 females, their median age was 63 (range, 43 -7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Postsurgical treatment with OXA and 5-FU/LFA improves the disease-free survival and overall survival (OS) of patients with resected stage III colon cancer (16,17). In addition, the combination of OXA with 5-FU/LFA (18) or RTX (19) showed a significant activity in chemonaive metastatic colorectal cancer patients, and the triplet combination of OXA, RTX, and 5-FU/LFA was tolerated and active also in heavily pretreated patients (20).…”
Section: Introductionmentioning
confidence: 99%
“…Postsurgical treatment with OXA and 5-FU/LFA improves the disease-free survival and overall survival (OS) of patients with resected stage III colon cancer (16,17). In addition, the combination of OXA with 5-FU/LFA (18) or RTX (19) showed a significant activity in chemonaive metastatic colorectal cancer patients, and the triplet combination of OXA, RTX, and 5-FU/LFA was tolerated and active also in heavily pretreated patients (20).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have shown high response rates for the combination of OXA with either FU/FA or RTX in MCRC (Cascinu et al, 2002;Seitz et al, 2002;Goldberg et al, 2004;Comella et al, 2005). Furthermore, the addition of OXA to a biweekly regimen of RTX and FU/FA proved manageable and active in heavily pretreated patients (Comella et al, 2002). Recently, several investigators have reported encouraging results with the addition of OXA to fluoropyrimidines during pelvic preoperative radiotherapy in LARC (Gerard et al, 2003;Rodel et al, 2003;Gambacorta et al, 2004a;Aschele et al, 2005;Sebag-Montefiore et al, 2005).…”
mentioning
confidence: 99%
“…In a series of clinical trials, raltitrexed has shown promising efficacy, favorable toxicity profile, and convenient administration schedule in patients with 5-FU-refractory mCRC as second-or third-line regimen. [4,8,9] Bevacizumab has been evaluated in various solid tumors. Several large phase III studies have demonstrated that the addition of bevacizumab to first-or second-line chemotherapy resulted in significant improvement in survival and response among patients with mCRC.…”
Section: Discussionmentioning
confidence: 99%